PENGUATAN KARAKTER GOTONG ROYONG MELALUI PEMBUATAN JAJANAN TRADISIONAL DALAM PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Noermala Nova Sirly Ludiana (Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya Provinsi Kalimantan Barat, 2025)
This study aims to describe the implementation of the Project to Strengthen the Profile of Pancasila Students (P5) in fostering the character of cooperation (gotong royong) through the making of traditional snacks among fifth-grade students (Phase C) at SDN 2 Rasau Jaya. This research employed a qualitative descriptive method. Data were collected through observation, documentation, and interviews. Observations were carried out by directly observing students during the action phase of the project. The findings indicate that the project activities successfully introduced students to various traditional snacks and the processes involved in making them. The results also show that the value of cooperation (gotong royong) was demonstrated by the participants throughout the project. Based on the findings, it can be concluded that the implementation of the Pancasila Student Profile Project effectively fosters the character of cooperation among fifth-grade students at SDN 2 Rasau Jaya.